Designing and evaluating the acceptability of a psychosocial and socioeconomic support package for people with drug-resistant tuberculosis in Johannesburg, South Africa - Ndiviwe Mphothulo; Marian Loveday (PLoS ONE, 2026)
Drug-resistant tuberculosis (DR-TB) is a global health problem that presents multifaceted challenges to people living with the disease. These challenges lead to sub-optimal adherence in some DR-TB patients who are then not cured of their TB. Besides the challenges associated with taking treatment, many patients with DR-TB also have to contend with psychosocial and socioeconomic challenges. The objective of this study was to develop a psychosocial and socioeconomic intervention for people with DR-TB in Johannesburg, South Africa, and evaluate if they find it acceptable. Guided by the Behaviour Change Wheel (BCW) and Perceptions and Practicalities Approach (PaPA) frameworks, and utilising a participatory research approach, We developed a support package with input from a qualitative needs assessment with DR-TB patients (n = 16) and family members (n = 8) and input from various stakeholders (n = 18), (health managers, clinicians and officials from social security departments). The support package was then evaluated for acceptability by patients who had successfully completed DR-TB treatment (n = 13) and their families (n = 6), using an exploratory qualitative method. Both successfully treated DR-TB patients and their family members found the intervention to be acceptable and believed it will reduce the barriers to retention in care that they faced during their treatment journey.